The maias : episodes from romantic life - Queirós, Eça de, 1845-1900 (New Directions, 2007)
Set in Lisbon at the close of the 19th century, this work is both a coming-of-age novel and a passionate romance. Newly translated by the acclaimed translator Costa, Eca de Queiross brilliant prose is brought to life for American readers for the first time.